TGF-β2 dictates disseminated tumour cell fate in target organs through TGF-β-RIII and p38α/β signalling - Bragado, Paloma (2013)
In patients, non-proliferative disseminated tumour cells (DTCs) can persist in the bone marrow (BM) while other organs (such as lung) present growing metastasis. This suggested that the BM might be a metastasis ‘restrictive soil’ by encoding dormancy-inducing cues in DTCs. Here we show in a head and neck squamous cell carcinoma (HNSCC) model that strong and specific transforming growth factor-β2 (TGF-β2) signalling in the BM activates the MAPK p38α/β, inducing an (ERK/p38)low signalling ratio. This results in induction of DEC2/SHARP1 and p27, downregulation of cyclin-dependent kinase 4 (CDK4) and dormancy of malignant DTCs. TGF-β2-induced dormancy required TGF-β receptor-I (TGF-β-RI), TGF-β-RIII and SMAD1/5 activation to induce p27. In lungs, a metastasis ‘permissive soil’ with low TGF-β2 levels, DTC dormancy was short-lived and followed by metastatic growth. Importantly, systemic inhibition of TGF-β-RI or p38α/β activities awakened dormant DTCs, fuelling multi-organ metastasis. Our work reveals a ‘seed and soil’ mechanism where TGF-β2 and TGF-β-RIII signalling through p38α/β regulates DTC dormancy and defines restrictive (BM) and permissive (lung) microenvironments for HNSCC metastasis.